The Influence of Recording, Inventorying, Reporting, and Application on The Quality of Financial Report : (Case of SIMAK-BMN) - Andansari, Ekowani; Mursidi, Mursidi; Jihadi, Muhammad (University of Muhammadiyah Malang, 2022)
The purpose of this study is to examine and analyze the effect of records, inventory, reports, and the usage of applications on the rate of financial reports of State-Owned Goods Financial Accounting Management Information System (SIMAK-BMN). Using a quantitative approach, 50 respondents filled online questionnaire and analyzed using multiple regression. The results of this study found that the better record, inventory, reporting, and application of SIMAK-BMN, the better the quality of financial reporting. Recording, reporting, and the implementation of the application can be improved in recording the movement and changes in BMN conditions, inventory, missing goods reports, and recording BMN mutation documents using complete and precise data.